Subsurface Mapping and Geotechnical Design for Landslide Mitigation - Hasan, Muhammad Fathur Rouf; Susilo, Adi; Sutan Haji, Alexander T.; Suryo, Eko Andi; Agung, P. A. Maha; Idmi, Mohammad Habibiy; Musta, Baba (Civil Engineering Journal, 2025)
The landslide near the PT Molindo Incinerator Unit poses a significant threat to the facility’s structural integrity. Without immediate mitigation measures, the incinerator building is at risk of collapse, potentially impacting adjacent settlements due to cascading structural failures. To reduce the risk of further instability, urgent geophysical investigation is required to characterize the subsurface lithology and assess the groundwater table conditions. A geoelectrical resistivity survey was conducted using the Schlumberger configuration across 8 measurement points along a 100-meter survey line, with 10-meter electrode spacing. The resistivity measurements ranged from 3.30 to 25 Ωm, which were interpreted as clay-rich layers; 26 to 167 Ωm, corresponding to sandy clay; and 167 to 15,944 Ωm, indicating bedrock. The potential slip zone is interpreted at an average depth of 20 to 25 meters, indicated by very low resistivity values with resistivity values between 3.30 and 25 Ωm. Field observations confirmed that the landslide materials predominantly consisted of clay soils, distributed within two distinct layers beneath the incinerator unit. The combined depth of the clay and overlying sandy layers was estimated to reach approximately 20-25 meters from the ground surface. To ensure the effectiveness of structural mitigation, a retaining wall must be designed to extend beyond this depth threshold. Numerical simulations using Slope/W software indicated that soil nailing techniques yielded safety factors ranging from 1.32 to 1.81 under static conditions and 1.22 to 1.43 under dynamic conditions. Predicted deformations ranged from 0.01 to 0.02 meters (static) and 0.02 to 0.03 meters (dynamic). These results suggest that soil nailing is a viable reinforcement method to stabilize slope movements, particularly during periods of high rainfall. Additional recommended mitigation strategies include the installation of surface and subsurface drainage systems to control water flow, constructing retaining structures to serve as physical barriers to soil movement, and using vegetative cover to enhance slope stability.